Univerzalnost čustva strahu v hebrejski in grški bibličnih tradiciji - Matjaž, Maksimilijan (Bogoslovni vestnik, 2025)
The discussion presents the special role of the emotion of fear as a fundamental dimension of the human experience of the transcendent. For Plato, fear is understood as the expectation of evil, which a person can overcomethrough knowledge, while for Augustine, fear is always connected with love. In the biblical texts, fear is not merely an irrational emotion but becomes the place of encounter with God. In the Hebrew and Greek biblical writings, the emotion of fear occupies a special position. It is mostly expressed by the terms yare’and phobéomai, as well as by the reassuring expressions ’al-tira’ and me phobouand their derivatives. It represents the most intense emotion, one that encom-passes the whole human being and surpasses him. Through the motif of fear, the multilayered nature of human response to divine transcendence and hu-man limitation is described. In the phenomenon of fear, the tension between opposites is simultaneously experienced, leading to an intensified awarenessof one’s own identity and of the presence of the transcendent. In this contribution, which builds on the author’s fundamental research on the Christological significance of the motif of fear in the Gospel of Mark, the role of the emotion of fear will be examined in more detail in the narrative of the healing of the woman with the haemorrhage (Mk 5:25-34), by exploring the relationship between fear and faith.
Keywords: Avguštin; čustvo; emotion; faith; fear; mysterium tremendum et fascinans; phobéomai; Platon; presežnost; strah; transcendence; vera; yare?; yare’